GP236 Fetal surgery for spina bifida a new development in the irish setting. (June 2019) - Joyce, John; Mullers, Sieglinde; Malone, Fergal; Boyle, Michael
Abstract : Introduction: Neural tube defects occur in approximately 1/1000 live births in Ireland, with myelomeningocele being the most common form. The current standard management in Ireland involves postnatal closure however access to fetal surgery services is increasing. The Management of Myelomeningocele Study (MOMS) compared prenatal and postnatal closure and showed reduced risk of death, decreased need for ventriculo-peritoneal shunting and improved motor function in the prenatal closure group. We present a case of fetal closure of myelomeningocele referred from our institution. Clinical Case: A 33-year-old female presented to the Rotunda for antenatal care in her second pregnancy following in vitro fertilisation abroad. Her first child was born with myelomeningocele and is a wheelchair user. She had been taking folic acid before and throughout this pregnancy. Antenatal ultrasound revealed a lemon-shaped head with Arnold-Chiari malformation, ventriculomegaly and myelomeningocele at L5/S1. Karyotype and microarray from amniocentesis were normal. She was referred to UCH London for fetal surgery consideration and ultimately underwent hysterotomy and closure of fetal myelomeningocele S1-S3 in Leuven, Belgium at 26 weeks gestation. The procedure involved successful closure of the dura and fascial layers, however, primary closure of the skin was not possible and so a silicone dermal regeneration template was applied to the defect. Improvement in head shape, ventricular size and Chiari malformation were noted on subsequent fetal ultrasound throughout the pregnancy. The patient presented with abdominal pain at 35+5 weeks gestation and proceeded to caesarean section. A live born male weighing 3.1 kg was delivered. He was vigorous with good lower limb movements and anal tone. The silicone graft was in position on the sacrum at delivery and peeled away spontaneously revealing a 2cm by 2cm patch of healthy granulating skin. There was no defect or leakage of cerebrospinal fluid. A silicone based wound dressing was applied and the infant was admitted to NICU for management. Enteral feeds were quickly established and postnatal cranial ultrasound was normal. He was transferred to Children's University Hospital for ongoing multidisciplinary team input. Discussion: This case represents the second patient to undergo fetal surgery for spina bifida from our institution, in a new partnership with UCH London and Leuven, Belgium. While the surgery is associated with risks of preterm delivery, intraoperative complications and uterine rupture, the potential for significantly better postnatal outcomes make it an important treatment option for some families and should be considered for discussion in suitable cases as they arise.